ANALISIS PENDAPATAN USAHATANI PADI SAWAH DENGAN POLA JAJAR LEGOWO DI DESA SIDERA KECAMATAN SIGI BIROMARU KABUPATEN SIGI SULAWESI TENGAH - Wengkau, Isna Meyke; Alam, Max Nur; Effendy, Effendy (AGROTEKBIS, 2017)
Sidera Village was one of the villages that were potentially to become producers of paddy (rice),located in Sigi Biromaru District. This research aims to determine the revenue ofrice farming with jajar legowo pattern inSidera Village Sigi Biromaru District Sigi Regency. This research was carried out in March to April 2016,the samples taken amounted to 31 respondents from the farmer population of 110 people who cultivate rice farming with jajar legowo pattern. The sampling method used was simple random sampling. The analysis of data used was revenue analysis. The results of the analysis showed that the average revenue gained by therice farmers in one planting season was Rp 10,102,095/1.15ha/PL with the average large of land owned by the respondents amounted to 1.15 ha,the total cost amounted to Rp 6,045,098, and the average revenue amounted to of Rp 16,147,193 so that in the right implementation of jajar legowo pattern, it is expected to provide benefits for the farmers.Â KeyWords: Farming, revenue, Rice, jajar legowo pattern.